Eosinophilia predicts poor clinical outcomes in recent-onset arthritis: results from the ESPOIR cohort - Sandrine Jousse-Joulin; Alain Saraux; Thierry Marhadour; Divi Cornec; Gilles Chiocchia; Valérie Devauchelle-Pensec; Gabriel J Tobón; Dewi Guellec; Morgane Milin; Olivier Vittecocq (RMD Open)
Objectives To determine the prevalence of eosinophilia in patients with recent-onset arthritis suggestive of rheumatoid arthritis (RA) and to describe their features and outcomes.Methods We performed an ancillary study of data from a French prospective multicentre cohort study monitoring clinical, laboratory and radiographic data in patients with inflammatory arthritis of 6 weeks to 6 months duration. We determined the proportion of patients with eosinophilia, defined as a count >500/mm3, at baseline and after 3 years. Features of patients with and without baseline eosinophilia were compared.Results Baseline eosinophilia was evidenced in 26 of 804 (3.2%) patients; their mean eosinophil count was 637.7±107/mm3. Baseline eosinophilia was ascribed to atopic syndrome in 6 of 26 (23.1%) patients. After 3 years, patients with eosinophilia had higher Health Assessment Questionnaire scores (0.9 vs 0.5, p=0.004), higher patient visual analogue scale activity score and morning stiffness intensity (p=0.05), and were more often taking disease-modifying antirheumatic drugs (p=0.02). Baseline eosinophilia was not associated with presence of extra-articular manifestations.Conclusions Eosinophilia is rare in recent-onset arthritis suggestive of RA, and is usually directly related to the rheumatic disease. Our data suggest that patients with mild eosinophilia at diagnosis could respond worse to the treatment than those without.